USING A LANDSCAPE APPROACH IN PLANNING ECOLOGICAL NETWORKS OF TERRITORIES (Scientific journal of the Fergana State University, 2024)
This article discusses the issues of creating an ecological network based on the landscape approach, which is one of the most effective forms of conservation and use of nature. The possibilities of organizing protected natural areas in accordance with the morphological units of landscapes are also analyzed.